Integrated transcriptomics and proteomics assay identifies the role of FCGR1A in maintaining sperm fertilization capacity during semen cryopreservation in sheep - Bai, Jiachen; Zhou, Guizhen; Hao, Shaopeng; Liu, Yucheng; Guo, Yanhua; Wang, Jingjing; Liu, Hongtao; Wang, Longfei; Li, Jun; Liu, Aiju; Sun, Wendell Q.; Wan, Pengcheng; et al. (Frontiers in Cell and Developmental Biology, 2023)
Semen cryopreservation is a promising technology employed in preserving high quality varieties in husbandry and is also widely applied in human sperm bank. However, the compromised quality, such as decreased sperm motility, damaged membrane structure as well as reduced fertilization competency has significantly hampered efficient application of this technique. Therefore, it is imperative to depict the various molecular changes found in cryopreserved sperm and identify the regulatory network in response to the cryopreservation stress. In this study, the semen was collected from 3 Chinese Merino rams and divided into untreated and programmed freezing group. After measuring the different quality parameters, the Ultra-Low RNA-seq and Tandem Mass Tag-based proteome were conducted in both the groups. The results indicated that the motility and viability of sperm in the FS group were significantly higher in comparison to the PS group. Moreover, three integrated methods were used for further analysis. The results suggested that the various differentially expressed genes and proteins were mainly enriched in leishmaniasis and hematopoietic cell lineage, and Fc Gamma Receptor Ia was significantly down-regulated in cryopreserved sperm both at mRNA and protein level in comparison with the fresh counterpart. In addition, top 5 gene and 22 proteins could form a distinct network in which genes and proteins were significantly correlated. Interestingly, FCGR1A also appeared in the top 25 correlation list based on O2PLS analysis. Hence, FCGR1A was selected for screening as the most potential differentially expressed candidate by the three integrated multi-omics analysis methods. Besides, Pearson correlation analysis indicated that the expression level of FCGR1A were positively correlated with sperm motility and viability. Subsequent experiment was conducted to identify the biological role of FCGR1A in sperm function. The results showed that both the sperm viability were significantly reduced in fresh and frozen sperm when FCGR1A was blocked. Moreover, the cleavage rate of embryos fertilized by FCGR1A blocked sperm was noted to be significantly lower in both fresh. In conclusion, our results revealed that the down-regulated membrane protein FCGR1A can potentially contribute to the reduced sperm fertility competency in the cryopreserved sheep sperm.